Influence of the cervical spine manipulation in the neck disability index in patients with chronic neck pain: A preliminary study - Miranda, Iã Ferreira; Facchini, Daniel; Manfio, Eliane Fátima (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Neck pain is one of the major problems managed by chiropractors, therefore its common the use of spinal manipulation to manage this problem. Objective: To evaluate the influence of Cervical Spine Manipulation (CSM) in the Neck Disability Index (NDI) of patients with chronic neck pain compared to a manipulative sham group. Method: 15 patients with chronic neck pain, were randomly assigned into one of two groups. Experimental Group (EG), with 8 patients, mean age of 30.6(13.7) years and Sham Group (SG), with 7 patients, mean age of 38.9(17.0) years. All the patients signed a Voluntary Informed Consent Document, approved by the university’s research ethics committee (n°555.015). The NDI was used to evaluate the outcome. The EG intervention was the CSM, performed 4 times, along a mean of 39.2 days. The SG was subjected to a similar cervical manipulative sensory experience, also performed 4 times, along a mean of 30.6 days. Paired and unpaired Student’s t-test was used to assess intra and inter group differences, respectively. Results: Statistically significant differences (p=0.000) were found for NDI between the pre and post-treatment evaluations of both the EG (26.3(5.0) % pre; 10.9(7.1) % post) and the SG (30.1(3.7) % pre; 18.4(5.3) % post). There were no significant differences for NDI in the pre-treatment between groups (p=0.122), however statistically significant differences were found in the post-treatment between the EG and the SG (p=0.039). Conclusion: The result shows that after the treatment period both groups showed improvement for NDI, however the CSM in the EG resulted in an improved outcome in the treatment of patients with chronic neck pain.